2012
DOI: 10.17221/37/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Biotech/GM crops in horticulture: plum cv. HoneySweet resistant to Plum pox virus

Abstract: Polák J., Kumar J., Krška B., Ravelonandro M. (2012): Biotech/GM crops in horticulture: Plum cv. HoneySweet resistant to Plum pox virus. Plant Protect. Sci., 48 (Special Issue): S43-S48.Commercialisation of Biotech/GM (Biotech) crops started in 1995. Not only field crops, but also horticultural transgenic crops are under development and are beginning to be commercialised. Genetic engineering has the potential to revolutionise fruit tree breeding. The development of transgenic fruit cultivars is in progress. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When graft inoculated with PPV-infected budwood or when vegetative ''root suckers'' from susceptible rootstocks have become infected, 'HoneySweet' trees have shown scarce and mild symptoms in the basal leaves near the source of infection. Systemic infection has generally not been detected, but when detected, it has been limited with mild symptoms that have diminished over multiple growing seasons (Polak et al, 2012). 'HoneySweet' trees have been shown to be resistant to all major strains of PPV (Ravelonandro et al, 2014).…”
Section: Ppv Resistancementioning
confidence: 99%
“…When graft inoculated with PPV-infected budwood or when vegetative ''root suckers'' from susceptible rootstocks have become infected, 'HoneySweet' trees have shown scarce and mild symptoms in the basal leaves near the source of infection. Systemic infection has generally not been detected, but when detected, it has been limited with mild symptoms that have diminished over multiple growing seasons (Polak et al, 2012). 'HoneySweet' trees have been shown to be resistant to all major strains of PPV (Ravelonandro et al, 2014).…”
Section: Ppv Resistancementioning
confidence: 99%
“…Polák et al (2012) reported that fruits of the genetically modified (GM) 'HoneySweet' , after joint infections of PPV with Plum dwarf virus (PDV) and/or Apple chlorotic leaf-spot virus (ACLSV), appeared to suffer no deterioration in either quality or quantity. Useniket al (2014) measured the levels of individual sugars and other compounds in the plum 'Brkinska češpa' (P. domestica L.), in fruits produced by trees suffering from short-term and long-term PPV infections, and determined that the fruits from long-term infected trees had the poorest pomological traits and also the most modified composition regarding nutritional and phenolic compounds Strick and Martin (2003) measured the effect of the Raspberry bushy dwarf virus on yield, fruit quality and growth of canes in the blackberry 'Marion' .…”
mentioning
confidence: 99%
“…Transgenic papaya with resistance to Papaya ringspot virus is the only commercialized GE fruit crop. Transgenic plum with resistance to Plum pox virus (PPV) was finally registered in 2011, but has not been commercialized in the United States because PPV is not spreading and the need for resistance is limited (Pol ak et al, 2012). Recently, 'Arctic R ' (nonbrowning) apple cultivars have been developed using RNAi-mediated intragenic technology (Okanagan Specialty Fruits, 2015), which subsequently provoked a new wave of the debate over GE fruits, and thus, commercialization has stalled.…”
mentioning
confidence: 99%